Telecoupling analysis of the Patagonian Shelf: a new approach to study global seabird-fisheries interactions to achieve sustainability - Raya Rey, Andrea Nélida (2020)
The Southwest Atlantic Ocean, particularly the extended Patagonian Shelf, constitutes a complex, globally-relevant ecosystem. It is a highly productive area, and it maintains a high diversity and abundance of seabird species. At the same time, the Patagonian Shelf experiences pressues, such as fisheries that have been identified as a main stressor for marine ecosystems worldwide, including being a principal cause of seabird population declines. Using the telecoupling framework - which incorporates natural and socioeconomic interactions over large distances - we present here a holistic look at the dynamics of threatened seabird- fisheries interactions for the Patagonian Shelf over space and time. Based on the best-available public data for seabird presence, we used machine learning and geographic information systems to model-predict the at-sea distribution of seabirds. Then, maps were overlaid with fisheries distributions to show spatial correlation and hotspots for co-occurrence between seabirds and fisheries. We found that even this remote corner of the Atlantic Ocean is globally connected to XXX nations and XXX other outside-stakeholders through fisheries. By identifying and characterizing the systems, flows, agents, causes and effects involved in this telecoupling process, we highlighted specific complexities, bottlenecks and sensitivities that must still be addressed to achieve both biodiversity conservation and management as well as fisheries sustainability not only in this study area, but worldwide.